Ergative in Mi=la=ras=pa'i rnam thar - Saxena, Anju (2024)
Classical Tibetans has been reported to be an aspectually split ergative language (Regamey, 1954; Dixon, 1979). although this is true only of some texts. DeLancey (1984) shows that case marking in modern Lhasa Tibetan has an active-stative pattern. The data given in Saxena (1988) suggest that there is a shift, in at least one modern dialect of modern Lhasa Tibetan, away from the active-stative pattern, and that the original ergative marker seems to function now as some sort of topic/emphasis marker2. In view of these various case marking patterns found in Tibetan, it will be interesting to see the case marking system in a text which is not so modern. The aim of this paper is to examine the 'ergative'3 pattern in Mi=la=ras=pa'i rnam Char 'the biography of Milarepa', an early vernacular Tibetan text. It will be shown that the Tibetan of the Mi=la=ras=pa has an active-stative case marking pattern. One of the limitations of working with a text is the nonavailability of all types of constructions that one would like in order to verify the claims; thus the suggestions made here should be taken as tentative.